Pengaruh Capital Structure, Profitability, Firm Size, Dan Firm Growth Terhadap Firm Value - Angelina Gabriela, Widyasari (Jurnal Paradigma Akuntansi, 2019)
The purpose of this study is to obtain empirical evidence regarding the effect of capital structure, profitability, firm size, and firm growth on firm value in manufacturing companies listed on the Indonesia Stock Exchange in 2015-2017. The samples were selected using the purposive sampling method and selected 66 companies as samples that met the criteria of 155 companies listed on the IDX. The results showed that capital structure, profitability, firm size, and firm growth had a significant effect on firm value. Capital structure, profitability, and firm size proved to have a significant and positive influence on firm value. This shows that the change in independent variables will be in line with firm value. While firm growth has a significant and negative influence on firm value. It means that the relationship between firm growth and firm value is inversely proportional.